A first assessment of potential stratigraphic traps for geological storage of CO2 in the Durban Basin, South Africa. (September 2017) - Hicks, Nigel; Green, Andrew
Highlights: First detailed seismo-stratigraphic assessment of individual potential saline aquifer reservoir systems within the offshore Durban Basin, eastern margin of southern Africa. Initial volumetric assessments of CO2 storage capacities for individual reservoirs within a frontier basin. Sequence stratigraphic correlation of reservoir systems within the Durban Basin with analogous hydrocarbon-bearing sequences in Mozambique. Comparison of defined storage capacity estimates for the Durban Basin with international best-practice capacity estimates for similar successions. Abstract: Within offshore frontier sedimentary basins, legacy data are important tools in basin-scale exploration for potential CO2 storage. We utilise single-channel 2D seismic reflection and well data obtained from the offshore Durban Basin, east coast South Africa, to provide new evidence of reservoir/seal pairs in saline aquifers that may represent potential storage sites for CO2 injection. Multiple, previously undefined and regionally pervasive stratigraphic traps have been mapped through a detailed seismo-sedimentary analysis. These include shelf-bound shallow-marine-sheet and deltaic sandstone packages of Turonian and Maastrichtian age respectively. Coeval with these laterally extensive shelf packages, multiple basin floor fan systems have been identified on the palaeo-slope. We further correlate these systems with analogous hydrocarbon-bearing sequences throughout a large region of the south-east African continental shelf. Using conservative assumptions, we propose that ∼327 Mt CO2 could potentially be stored in two laterally extensive shelf sand sequences, with a further potential for ∼464 Mt CO2 storage in basin floor fan systems in the distal basin.